Periodic orbits and non-integrability of Armbruster-Guckenheimer-Kim potential - Llibre, Jaume; Roberto, Luci Any Francisco [UNESP] (Springer Nature, 2013)
In this paper we study the periodic orbits of the Hamiltonian system with the Armburster-Guckenheimer Kim potential and its C1 non-integrability in the sense of Liouville-Arnold.
Keywords: Periodic solution; Averaging method; Non-integrability